Report of a Process Linking Basic Science Research with an Action Oriented Program for Research.... - Whitten Jr., Norman E.; Whitten, Dorothea S. (Human Organization)
Describes the anthropological research on the Puyo Runa grouping of Canelos Quicha culture in Ecuador. Focus of science research goals; Medical and financial assistance provided to the research subjects; Presentation of gifts of material culture by the minorities to the researchers.